2020
DOI: 10.3390/ani10071114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ovarian Circular RNAs and Differential Expression Analysis between MeiShan and Large White Pigs

Abstract: MeiShan and Large White pigs differ in their female fecundity. However, the mechanisms behind the gene expression and regulation that cause these differences remain unclear. In this study, we profiled circRNAs and identified 5,879 circRNAs from the ovaries of MeiShan and Large White pigs. Eighty-five circRNAs were differentially expressed between the two pig breeds. Of these, 37 were up-regulated and 48 were down-regulated in MeiShan pigs. Gene ontology enrichment analysis suggested that the differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…Liang et al show that circSCIN can be sponged with miR-133 and miR-148a/b, and its regulation determines the reproductive performance of Meishan and large white pigs [50]. CirceGFR, being a competitive endogenous RNA of miR-125a-3p, regulates FYN expression in mouse ovarian granulocyte cells [51]. Here, based on miRNA target site prediction analysis, we found that oar-miR-27a could be a target of novel_circ_0005497.…”
Section: Discussionmentioning
confidence: 71%
“…Liang et al show that circSCIN can be sponged with miR-133 and miR-148a/b, and its regulation determines the reproductive performance of Meishan and large white pigs [50]. CirceGFR, being a competitive endogenous RNA of miR-125a-3p, regulates FYN expression in mouse ovarian granulocyte cells [51]. Here, based on miRNA target site prediction analysis, we found that oar-miR-27a could be a target of novel_circ_0005497.…”
Section: Discussionmentioning
confidence: 71%
“…This finding uncovers litter size‐related circRNAs and provides potential candidate loci that may be informative for future pig breeding programs. As recent finding by Liang's research group, they identified 85 differentially expressed circRNAs in the ovarian tissues from MeiShan sows and Large White sows (Liang, Yan, Guo, & Tang, 2020). Furthermore, role investigation circRNAs showed that there is a circular RNA named circSCIN can target and sponge miR‐133 and miR‐148a/b affecting oestrogen secretion.…”
Section: Methodsmentioning
confidence: 88%
“…Its upregulated status in the uterus suggests that ATP2A3 helps in oviposition [ 34 ]. In addition, miR-133a-5p is a target of the circular RNA scinderin (circSCIN), which affects estrogen secretion [ 35 ]. These findings suggest that these miRNA-mRNA interaction networks may play key roles in the regulation of prolificacy in follicular phase ovaries in Yunshang black goats, thus providing new insights for further understanding the regulatory mechanisms of goat prolificacy.…”
Section: Discussionmentioning
confidence: 99%